Transformation in Indian Banks Through Corporate Governance-Emerging Challenges & Strategies for a New Gateway - Uppal, R. K.; Rani, Poonam (Prabandhan: Indian Journal of Management, 2010)
Strengthening the financial sector and improving the functioning of financial markets have been the core objective of the financial sector reforms in India. The significant transformation of the financial system in the country is clearly evident from the changes that have occurred in the financial markets, institutions and products. In 1990, the country witnessed an economic crisis leading to a fast decline in the GDP, a high rate of inflation, adverse BOPs due to a widening gap in the current account deficit and a decline in the foreign exchange reserves. The country had to borrow resources from foreign central banks and other foreign government agencies against the pledge of gold so as to avoid a default on international indebtedness. There were some banking sector deficiencies ahead of the economy, which were adversely affecting the economic growth of our country such as low productivity and profitability, public sector banks were incurring losses year after year, giving poor customer service, using outdated work technology etc. Keeping in mind all these distortions in the economic, financial and banking sectors, the government of India and the RBI thought it was necessary to introduce reforms in the financial and banking sector, so as to promote rapid economic growth and development with stability through the process of globalization, liberalization and privatization in the financial system to make the financial system more competitive and integrated with the world economy through internationalization of financial markets in the world.